Identification of sur2 mutation affecting the lifespan of fission yeast. Issue 12 (10th June 2021) - Kurauchi, Tatsuhiro; Matsui, Kotaro; Shimasaki, Takafumi; Ohtsuka, Hokuto; Tsubouchi, Satoshi; Ihara, Kunio; Tani, Motohiro; Aiba, Hirofumi
ABSTRACT: Yeast is a suitable model system to analyze the mechanism of lifespan. In this study, to identify novel factors involved in chronological lifespan, we isolated a mutant with a long chronological lifespan and found a missense mutation in the sur2 + gene, which encodes a homolog of Saccharomyces cerevisiae sphingolipid C4-hydroxylase in fission yeast. Characterization of the mutant revealed that loss of sur2 function resulted in an extended chronological lifespan. The effect of caloric restriction, a well-known signal for extending lifespan, is thought to be dependent on the sur2 + gene. Abstract : We isolated a novel chronologically long-lived mutant in fission yeast and identified sur2 missense mutation, which encodes a homolog of Saccharomyces cerevisiae sphingolipid C4-hydroxylase.